Brave new brain : conquering mental illness in the era of the genome - Andreasen, Nancy C. (Oxford University Press, 2001)
Nancy Andreasen, a leading neuroscientist who is also Editor-in-Chief of the prestigious American Journal of Psychiatry as well as the winner of the illustrious National Medal of Science, offers here a state-of-the-art look at what we know about the human brain and the human genome-and shows how these two vast branches of knowledge are coming together in a boldly ambitious effort to conquer mental illness. Scientists today know more about the brain than ever before, thanks to new imaging techniques and to discoveries in neuroscience and molecular biology. Andreasen gives us an engaging and readable description of how it all works, from the billions of neurons to the tiny thalamus to the moral monitor in our prefrontal cortex. She also shows the progress made in mapping the human genome, whose 30,000-40,000 genes are almost all active in the brain. In perhaps the most fascinating section of the book, we read gripping stories of the people who develop mental illness, the friends and relatives who share their suffering, the physicians who treat them, and the scientists who study them so that better treatments can be found.; This section covers four major disorders-schizophrenia, manic depression, anxiety disorders, and dementia-revealing what causes them, what happens to the mind and brain, and how the illnesses are treated. Finally, the book shows how the powerful tools of genetics and neuroscience will be combined during the next decades to build healthier brains and minds. Andreasen's bestselling The Broken Brain broke new ground in the public understanding of mental illness. Now, by revealing how combining genome mapping with brain mapping can unlock the mysteries of mental illness, she again offers general readers a remarkably fresh perspective on these devastating diseases-their nature, treatment, and possible future prevention.